Identifikasi Senyawa Curcumin, Bisdemethoxycurcumin dan Demethoxycurcumin Rimpang Curcuma xanthorrhiza Roxb. dan Curcuma longa L. dengan 1H NMR - Erwin Nur Indiarto; Tri Rini Nuringtyas; Yekti Asih Purwestri; Respati Tri Swasono; Yosi Bayu Murti (Universitas Sebelas Maret, 2018)
Curcumin and its derivates (Bisdemethoxycurcumin, Demethoxycurcumin) are natural dyes found in Curcuma xanthorrhiza dan Curcuma longa. Parmacologic evidence suggests all three are antioxidant, antiinflamatory, and anticancer. The objective of this research was to identify and measure the intensity of Curcumin compounds, Bisdemethoxycurcumin, and Demethoxycurcumin rhizome C. xanthorrhiza and C. longa by using 1H NMR spectra. Rhizome C.xanthorrhiza and C. longa collected from Wonogiri, Central Java. The rhizomes were dried in the oven at 40 °C and were powdered using a blender. The dried powder sample was extracted using methanol-d4 containing 0.01% TMSP and followed by ultrasonication for 15 minutes. The supernatant was separated from the solution by 10.000 rpm centrifugation for 10 minutes. The supernatant was transferred to NMR tube and analysed by using JEOL 500 MHz NMR. The obtained data were analysed by Mnova 12 software and Simca 14. Results of comparsion of 1H NMR spectra of both rhizomes with reference were identified Curcumin, Bisdemethoxycurcumin, Demethoxycurcumin compounds. The highest intensity all of three compound was found in Curcuma longa and with One way Anova test result obtained p<0,05. The two rhizomes show a good separation on the OPLS-DA scoreplot with Q2 82,1% indicating a good model. The study showed that Curcumin, Bisdemethoxycurcumin, Demethoxycurcumin compounds were found in both rhizomes and had different intensity